2022
DOI: 10.1101/2022.08.11.22278516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis of the amyotrophic lateral sclerosis spectrum uncovers genome instability

Abstract: Amyotrophic Lateral Sclerosis (ALS) is characterised by progressive motor neuron degeneration but there is marked genetic and clinical heterogeneity1. Identifying common mechanisms of ALS amongst this diversity has been challenging, however, a systematic framework examining motor neurons across the ALS spectrum may reveal unifying insights. Here, we present the most comprehensive compendium of ALS human-induced pluripotent stem cell-derived motor neurons (iPSNs) from 429 donors across 15 datasets including Ans… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…Although the degradation of circRNAs has hardly been studied, it has recently been shown that m6a methylation of RNA and activity of RNase L could promote the global elimination of circRNAs [3]. Interestingly, m6a hypermethylation of protein coding and non-coding RNA species have been observed in the spinal cord of sALS patients [78] and the expression of RNase L transcript is upregulated in iPSC-derived motor neurons from ALS patients [79]. In this respect, RNase L-mediated degradation of circRNA has been found to be necessary for the activation of protein kinase R (PKR) [80], which has been detected at higher levels in spinal cord [81] as well as in hippocampus from ALS patients [82], and its inhibition has been proposed as a promising therapeutic approach [82].…”
Section: Discussionmentioning
confidence: 99%
“…Although the degradation of circRNAs has hardly been studied, it has recently been shown that m6a methylation of RNA and activity of RNase L could promote the global elimination of circRNAs [3]. Interestingly, m6a hypermethylation of protein coding and non-coding RNA species have been observed in the spinal cord of sALS patients [78] and the expression of RNase L transcript is upregulated in iPSC-derived motor neurons from ALS patients [79]. In this respect, RNase L-mediated degradation of circRNA has been found to be necessary for the activation of protein kinase R (PKR) [80], which has been detected at higher levels in spinal cord [81] as well as in hippocampus from ALS patients [82], and its inhibition has been proposed as a promising therapeutic approach [82].…”
Section: Discussionmentioning
confidence: 99%